Japanese encephalitis virus capsid protein interacts with non-lipidated MAP1LC3 on replication membranes and lipid droplets. (23rd January 2021) - Sarkar, Riya; Sharma, Kiran Bala; Kumari, Anita; Asthana, Shailendra; Kalia, Manjula
Abstract : Microtubule-associated protein 1 light chain 3 (MAP1LC3) is a protein with a well-defined function in autophagy, but still incompletely understood roles in several other autophagy-independent processess. Studies have shown MAP1LC3 is a host-dependency factor for the replication of several viruses. Japanese encephalitis virus (JEV), a neurotropic flavivirus, replicates on ER-derived membranes that are marked by autophagosome-negative non-lipidated MAP1LC3 (LC3-I). Depletion of LC3 exerts a profound inhibition on virus replication and egress. Here, we further characterize the role of LC3 in JEV replication, and through immunofluorescence and immunoprecipitation show that LC3-I interacts with the virus capsid protein in infected cells. This association was observed on capsid localized to both the replication complex and lipid droplets (LDs). JEV infection decreased the number of LDs per cell indicating a link between lipid metabolism and virus replication. This capsid-LC3 interaction was independent of the autophagy adaptor protein p62/Sequestosome 1 (SQSTM1). Further, no association of capsid was seen with the Gamma-aminobutyric acid receptor-associated protein family, suggesting that this interaction was specific for LC3. High-resolution protein-protein docking studies identified a putative LC3-interacting region in capsid, 56 FTAL59, and other key residues that could mediate a direct interaction between the two proteins.